Effect of osteoprotegerin and osteoprotegerin ligand on osteoclast formation by arthroplasty membrane derived macrophages. - Itonaga, I; Sabokbar, A; Murray, D; Athanasou, N (2000)
OBJECTIVE: Osteoprotegerin ligand (OPGL) is a newly discovered molecule, which is expressed by osteoblasts/bone stromal cells. This ligand and M-CSF are now known to be essential for osteoclast differentiation from marrow and circulating precursors. This study examined whether OPGL and its soluble receptor osteoprotegerin (OPG), influenced osteoclast formation from human arthroplasty derived macrophages, to determine if the effects of OPGL and OPG on these cells could contribute to the osteolysis of aseptic loosening. METHODS: OPGL (+/- dexamethasone/M-CSF) was added to cultures of macrophages isolated from the pseudomembrane of loosened hip arthroplasties incubated on glass coverslips and dentine slices. OPG was added to cocultures of arthroplasty derived macrophages and UMR106 osteoblast-like cells. Osteoclast differentiation in long term cultures was assessed by expression of macrophage (CD14) and osteoclast markers (tartrate resistant acid phosphatase (TRAP), vitronectin receptor (VNR) and lacunar resorption). RESULTS: In the absence of osteoblastic cells, the addition of OPGL alone was sufficient to induce differentiation of macrophages (CD14(+), TRAP(-), VNR(-)) into TRAP(+) and VNR(+) multinucleated cells, capable of extensive lacunar resorption. OPG was found to inhibit osteoclast formation by arthroplasty macrophages in a dose dependent manner. OPG (100 ng/ml) more than halved the formation of TRAP(+) and VNR(+) cells and the extent of lacunar resorption in co-cultures of UMR106 cells and arthroplasty macrophages. CONCLUSIONS: This study has shown that macrophages, isolated from the pseudomembrane surrounding loose arthroplasty components, are capable of differentiating into osteoclastic bone resorbing cells and that OPGL is required for this to occur. OPG inhibits this process, most probably by interrupting the cell-cell interaction between osteoblasts and mononuclear phagocyte osteoclast precursors present in the pseudomembrane.